Equilibrium adsorption of nitrogen, oxygen, and argon on silver-exchanged hierarchical ETS-10 - Shrotri, Aadesh R.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Chemical and Engineering Data, 2023)
Silver-exchanged hierarchical ETS-10(Ag-H-ETS-10) was synthesizedusing Ag+ exchange with hierarchical Engelhard titanosilicate(H-ETS-10) using silver nitrate solution. The physical propertiesof the adsorbent were analyzed using X-ray diffraction (XRD), BETsurface area, nitrogen adsorption-desorption, pore volume,energy dispersive spectroscopy (EDS), and high resolution-transmissionelectron microscopy (HR-TEM). N-2 physisorption data confirmedthat a micro-mesoporous (bimodal) structure was created in the Ag-H-ETS-10.The equilibrium adsorbent data of pure gases N-2, O-2, and Ar were investigated in the temperature range from 288to 318 K up to 10 bar. The equilibrium adsorption capacity of Ag-H-ETS-10was found to be 1.12 mmol g(-1) for N-2,0.87 mmol g(-1) for O-2, and 1.09 mmol g(-1) for Ar at 298 K and & SIM;10 bar. & SIM;20% higheradsorption capacity was found for N-2 and Ar in Ag-H-ETS-10compared to Ag-ETS-10. The higher sorption capacity was attributedto the formation of a bimodal structure and & pi;-complexation interactionby the Ag cation, which allows a multilayer of N-2 and Armolecules. The Sips isotherm model was well fitted for the Ag-H-ETS-10experimental data among Langmuir, Freundlich, Toth, and Temkin models.The measured equilibrium adsorption data for Ag-H-ETS-10 can be usefulfor the O-2 purification process.

Effect of CTMABr/SiO2 molar ratio in synthesis of micro-mesoporous ZSM-5 composite and its application in 5-EMF (biofuel additive) formation - Manal, Prajakta N.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Bokade, Vijay V. (Environmental Progress and Sustainable Energy, 2024)
Synthesis of micro-mesoporous zeolite composite with optimum micro and mesoporosity is an emerging research area due to its wide applications, especially in bulk chemical or biomass transformations. It offers advantages in preserving zeolite crystallinity, creating mesoporosity and converting bulky molecules into valuable products. This work presents the process of preparing bimodal micro-mesoporous ZSM-5 using dual templates (CTMABr and TPABr). XRD, N2 adsorption-desorption, SEM, TEM, Si-29, and Al-27 NMR were used to analyze the two-dimensional micro-mesoporous ZSM-5. One-step synthesis of bimodal micro-mesoporous ZSM-5 features dual micro/mesoporosity by a marginal decrease in the crystallinity (71%). Micro-mesoporous ZSM-5 composite was found to be dependent on the optimum CTMABr/SiO2 molar ratio of 0.04 to 0.06. The micro-mesoporous ZSM-5 zeolite composite was evaluated for cascade synthesis of 5-EMF (methoxymethyl furfural- biofuel additive) from fructose and exhibited a five fold increase in 5-EMF yield to 24.2% as compared with parent ZSM-5 (4.6%).
Keywords: fructose; methoxymethyl furfural-biofuel additive; micro-meso composite; ZSM-5

Evaluating the preferential adsorption of N2 from a binary mixture of N2/O2 on extra-framework cations of zeolites: a computational and experimental study - Devasia, George; Nandanwar, Sachin U.; Krishnamurty, Sailaja (Physical Chemistry Chemical Physics, 2025)
Separation of N2 from a N2/O2 gas mixture is critical for various industrial/medical applications. Temperature/pressure swing adsorption is the top-notch industrial technology used for this separation, where zeolites are the materials used for adsorption. Zeolite X/Y with Li+ as an extra-framework cation is the best-known sorbent for N2 gas molecules. However, the present net zero emission scenario has made lithium a critical element, making it imperative to implement its alternative in various other technologies. In this context, the present work is a computational evaluation to identify a cation that can replace Li+ for preferential adsorption of N2 over O2. The DFT study, based on parameters such as selective adsorption energies of N2 over O2 and IR stretching frequencies of the adsorbed N2 and O2 molecules, identifies Mg2+, Ca2+, Sr2+, Co2+ and Zn2+ as potential cations. These cations have preferential adsorption for N2 over O2 by 10 kJ mol-1 or more. However, BOMD simulations reveal that only Mg2+, Ca2+, Co2+ and Zn2+ keep the N2 molecule bound at 300 K and the O2 molecule gets desorbed from these frameworks. The desorption temperature of N2 on Ca2+ and Zn2+ is 350 K and on Mg2+ is 400 K. These observations are corroborated by electronic charges on cations and molecular orbitals. Significantly, Ca2+ is identified to adsorb up to 2 N2 molecules, making it an ideal candidate for N2/O2 separation in place of Li+. To validate this, we have carried out an experimental study that showed a good N2 adsorption capacity of 2.1 mmol g-1 for Ca2+.